2016
DOI: 10.1177/0031512516637021
|View full text |Cite
|
Sign up to set email alerts
|

Handedness in Children With Autism Spectrum Disorder

Abstract: The left hemisphere is usually predominant in manual skills and language, suggesting a link between hand dominance and language. Studies of autism spectrum disorder show atypical handedness; however, few have examined language-handedness associations. Handedness, assessed by task performance, and standardized receptive and expressive language tests were completed in 110 autism spectrum disorder children (96 boys; M age = 8.3 years, SD = 3.8) and 45 typically developing children (37 boys; M age = 8.6 years, SD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Following intellectual testing, handedness was assessed using the Almli Handedness Assessment [Almli, Rivkin, & McKinstry, 2007; Knaus, Kamps, & Foundas, 2016]. This handedness assessment has previously been used on children with ASD between the ages of 3–17 [Knaus et al, 2016].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following intellectual testing, handedness was assessed using the Almli Handedness Assessment [Almli, Rivkin, & McKinstry, 2007; Knaus, Kamps, & Foundas, 2016]. This handedness assessment has previously been used on children with ASD between the ages of 3–17 [Knaus et al, 2016].…”
Section: Methodsmentioning
confidence: 99%
“…Following intellectual testing, handedness was assessed using the Almli Handedness Assessment [Almli, Rivkin, & McKinstry, 2007; Knaus, Kamps, & Foundas, 2016]. This handedness assessment has previously been used on children with ASD between the ages of 3–17 [Knaus et al, 2016]. The participant was seated in front of the experimenter and asked to complete 10 tasks using their hands with items presented at midline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of participant demographics, we considered whether studies included a clinically defined population, because adextrality (sometimes termed ‘pathological sinistrality’) has historically been associated with higher susceptibility to both congenital and acquired diseases (Coren & Halpern, ) and psychological disorders (Bradshaw‐McAnulty, Hicks, & Kinsbourne, ; Crow, Crow, Done, & Leask, ; Knaus, Kamps, & Foundas, ; Lindell & Hudry, ; Rodriguez et al., ; Satz, ). If this is true, we might observe either a greater proportion of adextrals amongst clinically defined samples, if these studies eschew handedness as an inclusion/exclusion criterion in order to facilitate recruitment; or alternatively a disproportionately low representation of adextrals if studies recognise the likelihood of adextrality and are therefore more likely to exclude adextrals.…”
Section: Introductionmentioning
confidence: 99%
“…Another field that can benefit from this independent understanding is neuroscience, where handdominance is commonly associated with several neurological factors [19]. For example, the authors of [20,21] found significant differences in the hand-dominance level of children with Autism Spectrum Disorder (ASD). A wearable camera that is able to differentiate between left and right hand is not only in line with biological and neurosciences perspective, but it also opens the doors to understanding hands as two interacting entities, centrally coordinated to achieve a particular goal.…”
Section: Introductionmentioning
confidence: 99%